ANALISIS PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SUBSEKTOR FARMASI YANG SUDAH TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Boman Lingga; Harman Malau (Universitas Muhammadiyah Jember, 2021)
Each company has a goal to enrich or increase profits as well as companies engaged in the food and beverage subsector which has a fairly broad industrial base in the country. In carrying out its operational activities the company in this sub-sector also deserves to think about aspects that enable the company to get support from various parties both in material such as investors, or non-material such as the creditor and local government trust. One important factor that must be examined is profitability. This study aims to determine how the effect of liquidity and solvency variables on profitability both partially and simultaneously. research will use descriptive methods. Data sources from research are secondary data obtained from the company's financial statements and annual reports. Secondary data is data obtained from other parties in the form of financial statements from companies, not collected directly by researchers. Then this study also uses purposive sampling to determine the sample that will be used in research. And will be accompanied by several hypothesis tests and data that will be processed to provide conclusions from the research that researchers do. After processing the data with several data analysis and test methods, it was found that liquidity has no influence on profitability; solvency has influence on profitability; and simultaneously liquidity and solvency have an influence on profitability